Analytical Nonstationary 3D MIMO Channel Model for Vehicle-to-Vehicle Communication on Slope - Kaizhen Liu; Zaixue Wei; Sibo Chen (International Journal of Antennas and Propagation)
Vehicle-to-vehicle communication plays a strong role in modern wireless communication systems, appropriate channel models are of great importance in future research, and propagation environment with slope is one special kind. In this study, a novel three-dimensional nonstationary multiple-input multiple-output channel model for the sub-6 GHz band is proposed. This model is a regular-shaped multicluster geometry-based analytical model, and it combines the line-of-sight component and multicluster scattering rays as the nonline-of-sight components. Each cluster of scatterers represents the influence of different moving vehicles on or near a slope, and scatterers are, respectively, distributed within two spheres around the transmitter and the receiver. In this model, it is considered that the azimuth and elevation angles of departure and arrival are jointly distributed and conform to the von Mises–Fisher distribution, which can easily control the range and concentration of the scatterers within spheres to mimic the real-world situation well. Moreover, the impulse response and the autocorrelation function of the corresponding channel is derived and proposed; then, the Doppler power spectrum density of the channel is simulated and analyzed. In addition, the nonstationary characteristics of the presented channel model are observed through simulations. Finally, the simulation results are compared with measurement data in order to validate the utility of the proposed model.